Sedation-related complications during anesthesiologist-administered sedation for endoscopic retrograde cholangiopancreatography: a prospective study - Zhang-Hagenlocher, Christine; Ganion, Nicole; Knebel, Phillip; Bopp, Christian; Brenner, Thorsten; Weigand, Markus A.; Sauer, Peter; Schaible, Anja (BMC anesthesiology, 2020)
Background: Patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) require adequate sedation or general anesthesia. To date, there is lack of consensus regarding who should administer sedation in these patients. Several studies have investigated the safety and efficacy of non-anesthesiologist-administered sedation for ERCP; however, data regarding anesthesiologist-administered sedation remain limited. This prospective single-center study investigated the safety and efficacy of anesthesiologist-administered sedation and the rate of successful performed ERCP procedures. - Methods: The study included 200 patients who underwent ERCP following anesthesiologist-administered sedation with propofol and remifentanil. Procedural data, oxygen saturation, systolic blood pressure (SBP), heart rate, recovery score, patient and endoscopist satisfaction, as well as 30-day mortality and morbidity data were analyzed. - Results: Sedation-related complications occurred in 36 of 200 patients (18%) and included hypotension (SBP < 90 mmHg) and hypoxemia (O2 saturation < 90%) in 18 patients (9%) each. Most events were minor and did not necessitate discontinuation of the procedure. However, ERCP was terminated in 2 patients (1%) secondary to sedation-related complications. Successful cannulation was performed in all patients. The mean duration of the examination was 25 ± 16 min. Mean recovery time was 14 ± 10 min, and high post-procedural satisfaction was observed in both, patients (mean visual analogue scale [VAS] 9.6 ± 0.8) and endoscopists (mean VAS 9.3 ± 1.3). - Conclusion: This study suggests that anesthesiologist-administered sedation is safe in patients undergoing ERCP and is associated with a high rate of successful ERCP, shorter procedure time, and more rapid post-anesthesia recovery, with high patient and endoscopist satisfaction.